Vocational training policies in Europe From 2000 To 2010 - Muniozguren Lazcano, María José (Avances en Supervisión Educativa, 2007)
After the 2000 compromise of the European Union Member States to make Europe into one of the most dynamic and competitive economic systems in year 2010, it was agreed that most education and vocational training systems had to be drastically transformed in a decade. However, factors such as a slowing demographic growth, cultural integration and population ageing may hinder the progress started since the end of XXth century.A further assessment of the situation in 2004 stated that development and cooperation at European level had notably improved in the context of the Lisbon process. 31 states were cooperating since then: 25 Member States of the European Union, 3 EU candidate countries and the 3 countries of the European Free Trade Association (Iceland, Norway and Liechtenstein). In 2006, new policies in vocational training cooperation are fostered  in Helsinki.The main conclusions to be drawn from the reports launched by the Education and Training 2010 Commission are disturbing, since differences between Northern and Southern countries in Europe are larger and advance in the development of human resources has been proved not to be as quick as initially expected. As a consequence, it's necessary to rate if the efforts to improve the education and vocational training systems since 2000 have reached the main actors of the expected change: students, workers, adults, teachers, local and regional policy-makers, advisory and regulatory bodies, educational authorities, representatives of trade unions and employers' organizations, and human resource managers.